Private sector responses to public investments and policy reforms: The case of fertilizer and maize market development in Kenya - Ariga, Joshua; Jayne, Thomas S. (International Food Policy Research Institute, 2009)
This paper documents the factors driving the impressive growth in fertilizer use and maize productivity in Kenya since the early 1990s up to 2007. The basic story is one of synergies between liberalization of input and maize markets and public investments in support of smallholder agriculture, leading to tangible private-sector investment in fertilizer retailing and maize marketing, which in turn has resulted in a 34 percent increase in smallholder fertilizer use per hectare of maize cultivated and an 18 percent increase in maize yields over the 1997–2007 period. There is also evidence of a reduction in maize marketing margins during this period. These developments have improved the welfare of rural and urban maize consumers, who constitute roughly 80 percent of Kenya’s population. While certain aspects of liberalization have also benefited maize-selling smallholder farmers, many other developments in the Kenyan agricultural sector have not. Events since 2007 call into question the sustainability of Kenya’s achievements in improving smallholders’ access to maize and fertilizer markets over the 1990–2007 period.